Comparative genomics of a cannabis pathogen reveals insight into the evolution of pathogenicity in Xanthomonas - Jacobs, Jonathan M.; Pesce, Céline; Lefeuvre, Pierre; Koebnik, Ralf (Frontiers in Plant Science, 2015)
Pathogenic bacteria in the genus Xanthomonas cause diseases on over 350 plant species, including cannabis (Cannabis sativa L.). Because of regulatory limitations, the biology of the Xanthomonas-cannabis pathosystem remains largely unexplored. To gain insight into the evolution of Xanthomonas strains pathogenic to cannabis, we sequenced the genomes of two geographically distinct Xanthomonas strains, NCPPB 3753 and NCPPB 2877, which were previously isolated from symptomatic plant tissue in Japan and Romania. Comparative multilocus sequence analysis of housekeeping genes revealed that they belong to Group 2, which comprises most of the described species of Xanthomonas. Interestingly, both strains lack the Hrp Type III secretion system and do not contain any of the known Type III effectors. Yet their genomes notably encode two key Hrp pathogenicity regulators HrpG and HrpX, and hrpG and hrpX are in the same genetic organization as in the other Group 2 xanthomonads. Promoter prediction of HrpX-regulated genes suggests the induction of an aminopeptidase, a lipase and two polygalacturonases upon plant colonization, similar to other plant-pathogenic xanthomonads. Genome analysis of the distantly related Xanthomonas maliensis strain 97M, which was isolated from a rice leaf in Mali, similarly demonstrated the presence of HrpG, HrpX and a HrpX-regulated polygalacturonase, and the absence of the Hrp Type III secretion system and known Type III effectors. Given the observation that some Xanthomonas strains across distinct taxa do not contain hrpG and hrpX, we speculate a stepwise evolution of pathogenicity, which involves (i) acquisition of key regulatory genes and cell wall-degrading enzymes, followed by (ii) acquisition of the Hrp type III secretion system, which is ultimately accompanied by (iii) successive acquisition of type III effectors.